Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2016)
A dataset containing 73428 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Leiothrichidae", "HasCoordinate is true", "HasGeospatialIssue is false" ] } The dataset includes 73428 records from 71 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0001609-160509122628363/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences